Risk-benefit assessment of foods the nut consumption case study - Assunção, Ricardo (2021)
Human diet may present both risks and benefits to consumers. Risk-benefit assessment (RBA) intends to estimate the benefits and risks for humans following exposure (or lack of exposure) to a particular food or food component and to integrate them in comparable measures. Significant methodological progress has been made and RBA utility is now recognised to support decision-making process in public health to prevent food-associated diseases and promote wellbeing in populations. Regular consumption of nuts, rich sources of cis-unsaturated fatty acids, fibre, vitamins, minerals, and a number of bioactive substances, is being associated with a reduction in all-cause mortality, particularly cardiovascular disease (CVD). At the same time, the occurrence of toxic food contaminants as mycotoxins in nuts, including the most potent carcinogenic aflatoxins (AFTs), has been reported by several authors worldwide. According to the National Food, Nutrition and Physical Activity Survey (IAN-AF 2015-16), the usual consumption of nuts by the Portuguese adults is 2.7 g/day. Some recent epidemiological studies (e.g. PREDIMED) suggested that a daily nuts consumption of 30 g could reduce the incidence of CVD. This presentation intends to establish the basis of the RBA methodology, using the nuts consumption as a case study. The health impact in terms of Disability-adjusted life years (DALY) of increasing nut consumption to 30 g/day by adult Portuguese population, when compared to the current intake, will be discussed. Integrating risks and benefits, around 5500 annual DALYs could be potentially saved by increasing the consumption of nuts to 30 g per day. These results suggest an overall beneficial health effect of increased nut consumption in Portugal. Therefore, it seems not advisable to reduce exposure to AFTs by recommending a reduced intake of nuts.